MAIN TIDAL POWER PLANTS IN THE WORLD: THE CASE OF THE PECÉM PORT POWER PLANTS, CE, BRAZIL (REMUNOM, 2025)
The burning of fossil fuels for energy consumption is responsible for 80% of greenhouse gas emissions. Replacing fossil fuels with low-emission primary sources represents one of the greatest challenges of the 21st century. Among renewable energy sources, tidal energy is one of the recently developed possibilities. In view of this, this study aimed to study the main tidal power plants in the world, focusing on the plant in Porto do Pecém-CE, Brazil. The study used an exploratory research method, with qualitative bibliographic review analyses, based on previously prepared materials used to compose the investigation. The scientific works were pre-selected and those considered most relevant were stored for better reading and understanding. The ABNT (Brazilian Association of Technical Standards) standards were followed to organize the references and citations. It was observed that, in the world, there are a number of plants that generate electricity from the tides, most of them operating through dams. Among them, the La Rance, Annapolis Royal, Kislaya Guba, Sihwa Lake and MeyGen plants stand out. Tidal energy consists of a form of energy capture carried out by taking advantage of the movement of the tides and their kinetic energy. The energy potential of tidal energy is determined mainly by the variations of the tides in coastal regions and by the efficiency of the technologies applied to obtain energy. In Brazil, the capture of energy from waves can be easily used, due to its extensive coastline of 7,300 kilometers that surrounds the country. It is concluded that the oceans have an enormous energy potential, which can be explored in several ways, among the main ones being the study of electricity generation. In Brazil, the application of tidal energy is possible.